The Aesthetics of Indirection: Intermittent Adjacencies and Subaltern Presences at the Borders of Europe (Cinéma & Cie. Film and Media Studies Journal, 2017)
Luca Guadagnino’s A Bigger Splash (2015), I argue, produces a sensorial registration of the presence of scattered subalterns. More importantly, an ‘aesthetics of indirection’ (con) gures the disturbing island-space between Italy and North Africa, where the intermittent appearance of subaltern subjects disturbs normative understandings of place and produces counter-intuitive understandings of relationality. The lmic construction of ‘intermittent adjacencies’ between subaltern presences and narrative protagonists produces gurations of disturbing relationalities between privilege and destitution, pleasure and pain, life and death. The logic of intermittent adjacencies left conspicuously un-integrated by the plot provide a sensorial and political provocation for thinking through the geopolitics of globalization in the context of the displacement of people.